The neural basis of human female mate copying: An empathy-based social learning process - ZHUANG, Jin-Ying (Institutional Knowledge at Singapore Management University, 2017)
We used functional magnetic resonance imaging (fMRI) to investigate the neural basis of human female mate copying.Consistent with previous mate copying effects, women's attractiveness ratings for target males increased significantlygreater after the males were observed paired with romantic partners versus ordinary friends, and this wasmainly accounted for by males being paired with attractive romantic partners. Attractiveness ratings for male targetswere lower when they were paired with an attractive opposite-sex friend. The fMRI data showed that the observationallearning process in mate copying recruited brain regions including the putamen, the inferior frontal gyrus, themiddle cingulate, the SMA, the insula, and the thalamus – areas overlapped with brain regions involved in empathy.The blood-oxygen-level-dependent (BOLD) signals in higher cognitive functions including the parieto-frontal network,as well as visual areas, were significantly more activated when women evaluated males in the friend versusromantic-partner context, whereas brain regions were not more active in the reverse comparison, suggesting thatless cognitive functions or as least no more functions were involved in evaluating the quality of target males inthe romantic-partner context than in the friend context. Further analysis indicated that specific brain regions relatedto the evaluation process of mate copying were associated with bilateral fusiform gyrus (FFA). Thus, results are consistentwith a view that mate copying is a domain-specific adaptation involving an empathy-based social-learningprocess that is also associated with reduced cognition.